2010
DOI: 10.1007/s11357-010-9166-4
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction attenuates the age-associated increase of adipose-derived stem cells but further reduces their proliferative capacity

Abstract: White adipose tissue is a promising source of mesenchymal stem cells. Currently, little is known about the effect of age and caloric restriction (CR) on adipose-derived stem cells (ASC). This is important for three reasons: firstly, age and CR cause extensive remodeling of WAT; it is currently unknown how this remodeling affects the resident stem cell population. Secondly, stem cell senescence has been theorized as one of the causes of aging and could reduce the utility of a stem cell as a reagent. Thirdly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Among the gene sets that were modified in the same direction in liver included ‘Ribosomal_proteins’ and ‘Ceramide_Pathway’, whereas reciprocal regulation of gene sets by CR and SRT2104 in muscle included ‘Boquest_CD31plus_vs_CD31minus_Up’, ‘Stemcell_Neural_Up’, and ‘Iglesias_E2Fminus_Up’ (Fig 2E ). Resident muscle stem cell side population as defined as CD31 (Pecam-1) negative lineage (Motohashi et al ., 2008 ) might be reciprocally affected by SRT2104 or CR (Schmuck et al ., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the gene sets that were modified in the same direction in liver included ‘Ribosomal_proteins’ and ‘Ceramide_Pathway’, whereas reciprocal regulation of gene sets by CR and SRT2104 in muscle included ‘Boquest_CD31plus_vs_CD31minus_Up’, ‘Stemcell_Neural_Up’, and ‘Iglesias_E2Fminus_Up’ (Fig 2E ). Resident muscle stem cell side population as defined as CD31 (Pecam-1) negative lineage (Motohashi et al ., 2008 ) might be reciprocally affected by SRT2104 or CR (Schmuck et al ., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…In [ 84 ], it was shown that CR reduces the percentage of ASC in the lin − SVF while also reducing colony-forming ability. Therefore, it was postulated that CR appears to have antiproliferative effects on ASCs that may be advantageous from the perspective of cancer.…”
Section: The Influence Of Ier On Humansmentioning
confidence: 99%
“…[63] The effects of CR is mediated by SIRT1, which participates in the extension of organismal life span by modulating DNA damage reactions. [64,65] White adipose tissue is the future of regenerative medicine because it serves as a source of mesenchymal stem cells. Age and CR leads to a wide remodeling of white adipose tissue but how this remodeling in uences the resident stem cell population requires more studies.…”
Section: Cells Stemnessmentioning
confidence: 99%